Dyskinesias induced by subthalamotomy in Parkinson's disease are unresponsive to amantadine - Merello, Marcelo Jorge (2006)
Background: Dyskinesias are a transient but severe complication of subthalamotomy in some patients. Patients and methods: Three patients with Parkinson’s disease undergoing bilateral micro-recording guided surgery of the subthalamic nucleus (STN) are described; deep brain stimulation (DBS) was used in one case, and subthalamotomy in the other two. Prior to surgery, levodopa induced dyskinesia had improved (⩽50%) under treatment with amantadine (400 mg/day, po) in all three patients. The patient treated with DBS developed severe dyskinesia a few days after discharge and began self medication with amantadine but showed no improvement. This suggested a possible lack of response to amantadine for treatment of dyskinesias induced by surgery of the STN. Results: Both patients treated with bilateral subthalamotomy developed unilateral choreoballistic movements immediately after surgery, despite not taking levodopa (L-dopa). Patients were scored using the dyskinesia scale and started treatment with 400 mg amantadine (po) for 4 days within the first postoperative week with no effect on dyskinesia score or its phenomenology. Amantadine was therefore discontinued. One month after surgery both patients were free of involuntary movements with an improvement of about 60% in the “off” state UPDRS motor score. Six month follow up showed maintained antiparkinsonian benefit, without need for levodopa treatment and complete absence of dyskinesia. Conclusion: The present findings suggest that: (i) amantadine probably exerts its anti-dyskinetic effect by acting on the “indirect” pathway; (ii) the pathophysiological mechanisms of subthalamotomy induced dyskinesias may differ from those involved in L-dopa induced dyskinesias; (iii) dyskinesias induced by STN surgery resolve spontaneously as compensatory mechanisms develop.